MODULAR AND SELF-ORGANIZING CONNECTIONIST SYSTEMS: TOWARD HIGHER LEVEL INTELLIGENT FUNCTIONS - Madani, Kurosh (International Journal of Computing, 2014)
Recent advances in “neurobiology” allowed highlighting some of key mechanisms of animal intelligence. Among them one can emphasizes brain’s “modular” structure and its “self-organizing” capabilities. The main goal of this paper is to show how these primary supplies could be exploited and combined in the frame of “soft-computing” issued techniques in order to design intelligent artificial systems emerging higher level intelligent behavior than conventional Artificial Neural Networks (ANN) based structures.